Consumer behavior with Artificial intelligence products - Xue, Manman (International Journal of Global Economics and Management, 2023)
In today's era, science and technology have made rapid progress, which makes the rapid formation of the Internet era, and promotes the wide application of artificial intelligence in the commercial field. With the rapid development of e-commerce, online shopping has become more and more popular, and online shopping has become the way of shopping chosen by more and more people. In the context of the continuous development of artificial intelligence, for the online shopping industry, actively citing artificial intelligence is very beneficial to the development of the industry. However, considering that consumers' acceptance of intelligent customer service is different, this artical will use Technology Acceptance Model to analyze the usefulness and ease of intelligent customer service, and confirm consumers' acceptance of intelligent customer service in the process of online consumption. The remainder of this paper is organized as follows.